210k views
4 votes
5x - 2y = -26
-7x + 4y = 40
Show your work?​

User Fuzzbone
by
5.2k points

1 Answer

5 votes

Answer:

x = -4, y = 3

Explanation:

In one equation (let's use the top one), solve for one of the variables (let's solve for y first).

5x - 2y = - 26 --> -2y = -5x - 26 --> y = (5/2)x + 13

Now, substitute ((5/2)x + 13) in for y in the second equation.

-7x + 4((5/2)x + 13) = 40 --> -7x + 10x + 52= 40 --> 3x = -12 --> x = -4

Then, subtitute that in to one of the equations.

5(-4) - 2y = -26 --> -20 - 2y = -26 --> -2y = -6 --> y = 3

User YuKagi
by
5.0k points